Attention-Seeking Behavior and Loneliness as Contributing Factors to Problematic Social Media Use: A Study of Early Adults in Jabodetabek - K. Brantakesuma, Rasikhansa; Rosalina (Lafadz Jaya Publisher, 2024)
This study investigates the influence of attention-seeking behavior and loneliness on problematic social media use among early adults who are active social media users in the Jabodetabek area. A total of 201 participants were selected through self-selected surveys. The instruments used include the Bergen Social Media Addiction Scale (BSMAS) for measuring problematic social media use, the Attention-Seeking Scale for assessing attention-seeking behavior, and the UCLA Loneliness Scale version 3 for evaluating loneliness. Multiple linear regression analysis revealed that attention-seeking behavior and loneliness have a significant impact on problematic social media use, with an R² of 0.661, indicating a 66.1% contribution. The data analysis showed that attention-seeking behavior (p-value < 0.001, t = 8.185) and loneliness (p-value < 0.001, t = 6.086) both significantly influence problematic social media use. In conclusion, both attention-seeking behavior and loneliness significantly contribute to problematic social media use among early adults in Jabodetabek.